Implementation of Internet Safety and Health Monitoring (K3) based on Internet of Things (IoT) - Qomariyatus Sholihah; Dewi Hardiningtyas; Stephan Adriansyah Hulukati; Wahyudi Kuncoro (International Journal of Health and Pharmaceutical (IJHP), 2024)
The use of computers in the future can dominate human work and defeat human computing capabilities such as controlling electronic equipment remotely using internet media, IoT (Internet of Things) allows users to manage and optimize electronics and electrical equipment that uses the internet for Automation of Occupational Health and Safety (OHS) Internet-Based Electricity Of Things (IoT). Design of Automation Occupational Health and Safety (OHS) Electricity Based on the Internet of Things (IoT). which is used to test the installation of research instrument equipment. This needs to be done to ensure that the installation and research instruments function properly at the actual time of the experiment. Devices that have been made by the researchers can work well as expected, where the automation of the protection of Occupational Health and Safety (OHS) Internet-Based Electricity of Things (IoT) so that it can provide initial help in the event of work accidents caused by gas leakage and fire monitored online by panel space operators. That's because most of the interactions between IoT devices with Users occur in digital form. Besides, expertise in reading digital data to support the decision-making process is also very crucial from the results of the calculation of the implementation of data monitoring of Occupational Health and Safety (OHS) Internet-Based Electricity of Things (IoT) with an average of 3.54 and the eigenvalues value approaching 29.4, indicating that the majority of workers in a private hospital in Malang City strongly agrees with the application of Internet If Things in the private hospital in Malang City Environment.